Experimental study of fixed and fluidized beds of PCM with an internal heat exchanger. (5th August 2016) - Izquierdo-Barrientos, M.A.; Fernández-Torrijos, M.; Almendros-Ibáñez, J.A.; Sobrino, C.
Graphical abstract: Highlights: Measured heat transfer coefficient between a bed of PCM and an immersed coil. Three different helical coil heat exchangers tested. Higher heat transfer coefficient for the fluidized bed than for the fixed bed. Higher heat transfer coefficient for the PCM than for a sensible heat material. Abstract: This work presents the results of experiments performed in a thermal energy storage tank filled with particles, which was heated using hot air and then discharged with a cold water stream circulating inside a heat exchanger immersed in the bed. Both fixed- and fluidized-bed configurations were studied. The materials used were sand, which is a material commonly employed in sensible heat storage, and a granular phase change material (PCM), in which the phase change occurs over the temperature range of 40–50 °C. Three different heat exchangers with different helical coil geometries were tested by measuring the temperatures in the bed and at the water inlet and outlet. Higher heat transfer coefficients between the bed and the water flow and higher heat exchanger effectiveness were observed for the heat exchanger with the greatest distance between coils, as it allows better contact between the bed particles and the heat exchanger surface when the particles are fluidized.